Business strategy evaluation using scenario planning in pt bukit asam (persero) tbk - Wicaksono, Setiadi; Sunitiyoso, Yos (The Indonesian Journal of Business Administration, 2016)
Abstract â€“ PT Bukit Asam (Persero) Tbk has develop long term strategic plans based on vision â€œTo be a world-class energy company that cares about the environmentâ€. It was single scenario that focus on developing company value chain on coal mining, power, and coal beneficiation in order to align with the vision. Challenge come, when coal industry facing a great uncertainty that gives high impact in Coal Price and Environmental Regulation. Single scenario could not be applied to survive in those uncertainty future. Scenario planning is a way to develop the groundwork for a strategic plan that doesnâ€™t place the companyâ€™s future on the emergence of a single â€œmost likely scenarioâ€. Instead it recognizes that at any point in time, there is an array of possible futures that could potentially unfold. Â Based on uncertainty factor in Coal Price and Environmental Regulation, PTBA develop 4 scenario planning: Dark Age (Low Coal Price â€“ Loose Environmental Regulation), A New Hope (High Coal Price â€“ Loose Environmental Regulation), Life in Transition (Low Coal Price â€“ Tight Environmental Regulation), and The New World (High Coal Price â€“ Tight Environmental Regulation). Each of scenario planning has certain implications, which need certain option/strategy to deal with it. It also equipped with early warning signal as monitoring tool the emergence of one scenario in which management should prepare certain option/strategy to adapt with upcoming scenarioÂ Keyword: Scenario planning, Coal Industry, Coal Price, Environmental Regulation